The Implementation of Independent Learning-Independent Campus (MBKM) Teaching Assistance in Education Units Towards Students' Soft Skills and Hard Skills - April Ade Sunia; Baso Jabu; Samtidar Samtidar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
The objective of this research was to find out whether the implementation of Independent Learning-Independent Campus (MBKM) teaching assistance in education units has an impact on students' soft skills and hard skills. This research took place at the State University of Makassar, Faculty of Language and Literature. The participants of this research were the students of the English Education Study Program. The researchers used a descriptive qualitative method with a purposive sampling technique to select the participants. The instrument of this research was an interview. Based on the result of the interview, the researchers found that the implementation of MBKM can improve students’ soft skills and hard skills. Furthermore, the researchers concluded that the implementation of independent learning-independent campus (MBKM) teaching assistance in education units can improve students' soft skills and hard skills.